Registration of 'KSUZ 0802' Zoysiagrass. Issue 2 (27th April 2017) - Chandra, A.; Fry, J. D.; Genovesi, A. D.; Meeks, M.; Engelke, M. C.; Zhang, Q.; Okeyo, D.; Moss, J. Q.; Ervin, E.; Xiong, Xi; Milla-Lewis, S.; Brosnan, J.T.; et al.
Abstract : KSUZ 0802 (Reg. No. CV‐282, PI 678793) is a fine‐textured, cold‐tolerant zoysiagrass ( Zoysia spp.) hybrid co‐developed and jointly released by Texas A&M AgriLife Research, Dallas, TX, and the Kansas Agricultural Experiment Station, Manhattan, KS. KSUZ 0802 is an F1 interspecific hybrid developed in 2001 from a cross between Zoysia matrella (L). Merr. 'Cavalier' and an ecotype of Z. japonica Steud. named Anderson 1, a derivative of 'Chinese Common'. After years of testing (2004 –2008) for turf quality and winter survival at Manhattan, KS, KSUZ 0802 was advanced to a nine location test (2009 –2012) in the transition zone (Wichita and Manhattan, KS, Columbia, MO, Fletcher and Jackson Springs, NC, Stillwater, OK, Knoxville, TN, Virginia Beach and Blacksburg, VA, and Dallas, TX. The freezing tolerance, spring green‐up, and fall color retention of KSUZ 0802 is equivalent to 'Meyer', but KSUZ 0802 has a finer leaf texture. KSUZ 0802 is also superior to Meyer for turf quality and resistance to bluegrass billbug damage. KSUZ 0802 is well suited for use on golf course fairways and tees, home lawns, and other recreational areas in the transition zone.